133k views
3 votes
Multiply (6v+5)(412-2v+7) then simplify the expression

2 Answers

6 votes
simplified answer,, -12v^2+2504v+2095
User Mahoni
by
5.0k points
3 votes

Answer:
=-12v^2+2504v+2095

Explanation:

Given the expression:


(6v+5)(412-2v+7)

You need to apply Distributive property, but first remember the multiplication of signs:


(+)(+)=+\\(+)(-)=-\\(-)(-)=+

Then:


(6v+5)(412-2v+7)=2472v-12v^2+42v+2060-10v+35

Finally, you can simplify the expression by adding the like terms:


=-12v^2+2504v+2095

User Mkafiyan
by
5.1k points